The Influence of Live Shopping on Purchase Decisions among TikTok Shop Users in Indonesia - Aldina Esty Purwanti (Universitas Sains dan Teknologi Komputer, 2026)
The growth of digital commerce has pushed the use of social media via live shopping features, so there is a more direct, kind of immediate interaction between sellers and consumers, and this can strengthen purchase decisions. Here, the study is trying to analyze how live shopping affects purchase decisions among TikTok Shop users in Indonesia. This research uses a quantitative method, and the data were collected using a questionnaire based on a Likert scale and then processed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The results show that live shopping has a positive and statistically significant impact on purchase decisions (β = 0.683; p < 0.001). In particular, real-time interaction along with information clarity and responsive communication are shown to improve trust and also help speed up consumer decision-making. Overall, this study contributes by placing live shopping as the key variable within the purchase decision model, and it provides novelty for digital marketing research, while also giving practical input for businesses and platforms that want to optimize interaction-based strategies.